Dynamics of Performance Appraisal among Staff in the Ministry Of Education and Training in Lesotho - Makhetha, Isaiah M. (International Journal of Scientific Research and Management (IJSRM), 2024)
The objective of this study was to determine whether employees are appraised in an objective manner in the Ministry of Education and Training in Lesotho and also to establish whether performance appraisal brings about intended results in this ministry. This investigation adapted a mixed-methods approach. The population comprised 100 employees of the Ministry of Education and Training. A sample of 50 officers was selected from the population using proportionate stratified random sampling. Data were collected through a use of a questionnaire. The reliability of this instrument was ascertained through employing the split halves which consequently yielded the reliability coefficient of 0.82. Chi-square analysis revealed that employees are appraised in an objective manner in the Ministry of Education and Training in Lesotho.  On the other hand, chi-square analysis showed that performance appraisal does not bring about intended results in this ministry. On the basis of these results, it was concluded that performance appraisal is conducted in an objective manner in the Ministry of Education and Training in Lesotho and also that performance appraisal does not bring about intended results in this Ministry.